Severe cerebral white matter lesions in ischemic stroke patients are associated with less time spent at home and early institutionalization. Issue 8 (21st October 2015) - Sibolt, Gerli; Curtze, Sami; Melkas, Susanna; Pohjasvaara, Tarja; Kaste, Markku; Karhunen, Pekka J.; Oksala, Niku K. J.; Erkinjuntti, Timo
Abstract : Background: Cerebral white matter lesions are one imaging surrogate for cerebral small vessel disease. These white matter lesions are associated with increased morbidity and mortality in both the general population and ischemic stroke patients. Aims: To investigate whether severe white matter lesions in a cohort of ischemic stroke patients are associated with fewer days spent at home and earlier permanent institutionalization. Methods: We included 391 consecutive patients aged 55–85 years with ischemic stroke admitted to the Helsinki University Central Hospital (the Stroke Aging Memory cohort) with a 21‐year follow‐up. Hospitalization and nursing home admissions were reviewed from national registers.white matter lesions were rated using magnetic resonance imaging performed three‐months poststroke, dichotomized as none‐to‐moderate and severe. Kaplan–Meier plots log‐rank and binary logistic regression (odds ratio) and Cox multivariable proportional hazards model were used to study the association of white matter lesions with days spent at home and the time of permanent institutionalization. Hazards and odds ratio with their 95% confidence intervals are reported. Results: Severe white matter lesions were associated with fewer days spent at home, and more frequent, and earlier permanent institutionalization (1487 vs. 2354 days; log‐rank P  < 0·001).After adjusting for significant covariates from univariable analyses, severe white matter lesions were associated with fewer days spent at home (odds ratio 1·62; confidence interval 1·16–2·25), permanent institutionalization within five‐years (odds ratio 2·29; confidence interval 1·23–4·29), and increased hazards ratio of permanent institutionalization during 21 years of follow‐up (1·64; confidence interval 1·119–2·26). Conclusions: After ischemic stroke, patients with severe white matter lesions spend fewer days at home and become permanently institutionalized earlier, especially within the first five‐years.